ACHIEVING GENDER EQUALITY, ECONOMIC JUSTICE AND COMPETITION LAW IN INDIA - Kashyap, Amit; Jameel, Mohd. (International Journal of Research -GRANTHAALAYAH, 2018)
The Millennium Development Goals (MDG) on gender equality can be achieved by mainstreaming a gender perspective and promoting women’s economic empowerment. Punjab has almost become synonymous with the low status of women, patriarchal society, feudal customs and values, social polarization along caste lines, high illiteracy, and poverty. The secondary status of women in Punjab coupled with an oppressive caste system and grinding poverty has robbed the women of their rights and a life of dignity, which were envisaged by the framers of the Constitution. The issue of gender equality has acquired a global character, and therefore, there is a need for the Civil Society to actively participate and enable the women to fight for their rights. The United Nations has included the issue of gender mainstreaming in the Millennium Declaration and ’promoting gender equality and empowerment of women’ is one of the Millennium Development Goals (MDGs). Improved gender sensitivity could be achieved by adopting a proactive approach towards achieving gender economic justice. Therefore achieving gender equality requires two complementary approaches–mainstreaming a gender perspective and promoting women’s economic empowerment.